Experimental Analysis of Various Materials on Custom-Fit Ankle Foot Orthosis - Dishank aryan, Rithwik M Nair, Yash singhania , (International Journal of Advanced Science and Technology, 2020)
Traditional Ankle Foot Orthoses (AFOs) are designed to work for a range of patients. They could not tend to the needs of comfort and orthotic functions arising due to individual differences. This can be solved by custom fit AFO’s but the current methods involve a lot of manual labor. Rapid Prototyping and reverse engineering can be used on 3-D parts or models designed in CAD software. Through 3-D scanning, we design an AFO’s customized to an individual foot’s anatomy. The scanned data was used to design an AFO structure. The designed structure was virtually tested for different materials and an analysis of the same was done.